Strategy Work in a Finnish industrial SME company : A Case study - Hyyryläinen, Antti (My University, 2023)
Balanced scorecards and strategy maps by Kaplan & Norton are strategic management tools for organizations to develop their resources to be more efficient. Balanced score-cards are used to measure the success of factors that wanted to measure to see improve-ments and a strategy map is a visual chart that explains the causation between four differ-ent perspectives which are in the center of the balanced scorecard tool. The idea is to fulfill the objectives for the greater vision to be achievable. This thesis’s main objective is to describe the first strategy process of the selected case company. During the process, a model of a strategy map and balanced scorecard was cre-ated. The study was conducted as a case study and the research strategy used was an ethno-graphic action study. Material for the study was generated during the strategy process in eight different strategy sessions, led by external consultants in spring 2019, and written down to a Howspace platform for later to be used in this study. The results of this study may be used for further development of the strategy process for the case company.
Keywords: strategies; balanced scorecard; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development